Chemical characterization and bioactivity of phenolics from Tieguanyin oolong tea. Issue 7 (15th May 2019) - Wang, Yuefei; Kong, Dedong; Gao, Yuanyuan; Ying, Le; Huang, Qianfei; Xu, Ping
Abstract: Phenolics are the main bioactive components in tea and greatly contribute to human health. Three phenolic‐enriched extracts, the ethyl acetate fraction (TEF), n‐butanol fraction (TBF), and water fraction (TWF), were obtained from Tieguanyin oolong tea, which is considered a typical type of semi‐fermented tea. The chemicals in the extracts and their antioxidant activity and cytotoxicity against 4T1 breast cancer cells were investigated in the present work. TEF was found to have the highest contents of phenolics, flavonoids, procyanidins, sugars, and catechin monomers. Meanwhile, TEF exhibited the strongest antioxidant capacity, which may be due to its abundant bioactive compounds, as validated by Pearson correlation and hierarchical clustering analysis. Furthermore, TEF showed greater inhibition of the growth of 4T1 murine breast cancer cells than TBF and TWF. Practical applications: Fermentation during the processing of oolong tea causes many alterations in polyphenols, leading to different bioactivities. In the present work, three phenolic‐enriched extracts, the ethyl acetate fraction (TEF), n‐butanol fraction (TBF), and water fraction (TWF), were obtained from Tieguanyin oolong tea. Further tests showed that TEF and TBF from Tieguanyin oolong tea possessed remarkable antioxidant activity and inhibitory potential inhibition of the growth of 4T1 murine breast cancer cells in vitro due to their main bioactive compounds, including phenolics and flavonoids. Thus, the phenolic‐enriched extracts from Tieguanyin tea are expected to have a potential application in the food and pharmaceutical industries after further study.